Igniting deliberation in high stake decisions: A field study - Andreas Hefti; Peiyao Shen; King King Li (University of Zurich, Department of Economics, 2021)
We conduct a large scale randomized field experiment to study whether providing recipients - 42,454 Chinese households in a rural area - with information on the costs of a real decision they make can help to improve the quality of their choices. The decisions are of high financial impact, as the objects of deliberation - air conditioners - have upfront prices exceeding the average monthly salary of a household. Besides providing nominal cost information, we conduct two additional treatments, where we either present the same information by making the real opportunity costs salient, or by administering the information via a quiz. The former aims at facilitating the comparison of effective costs, while the latter aims at enhancing attention and cognitive involvement. We find that providing cost information substantially affects the choices made, and reduces the decision mistakes, in particular in the two additional treatments.
Keywords: D12; D83; L68; Q41; Q48; 330; Information provision; opportunity costs; decision mistakes; involvement; energy efficiency